Hardware Communications: An Open-Source Ethernet Switch Implementing the Parallel Redundancy Protocol - André Torres; Rodrigo Piedade; Filipe Moutinho; Luis Gomes (Applied Sciences)
Ethernet communications are widely used in many areas, and redundant protocols like the Parallel Redundancy Protocol (PRP) and High-Availability Seamless Redundancy (HSR) were created to make these communications more reliable. These protocols’ goal is to have a zero-delay network reconfiguration time. In order to achieve this, both protocols have a double network, and a copy of every packet will be present on the network. Upon packet reception, it will be verified if it is new or has been received before, being discarded if it is duplicated. This paper presents an open-source Ethernet switch, the REDSwitch, capable of implementing the PRP protocol, besides working as a regular switch. This Ethernet switch is based on an open-source project and was developed further, including a hash table with an aging mechanism, to store the received packets and allow duplication analysis. The REDSwitch is capable of dealing with the IPv4 protocol, IEEE 802.1Q, and implementing the PRP protocol. Specified in Verilog and SystemVerilog, it was designed to be implemented on field-programmable gate array (FPGA) devices.